Symptomatic cerebral ependymal cyst: a case report - Paharudin, Rauf; Mohd Nor, Aidil; Chan, Kin Hup; Awang, Mohamed Saufi; Mustapha, Fadhli (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Cerebral ependymal cyst is a rare benign neuroepithelial cyst. We report a case of cerebral ependymal cyst in a 62-year-old lady who presented with status epilepticus. She gave history of progressive right occipital headache over a year. Magnetic Resonance Imaging of the brain showed a large occipital cyst. She underwent a right craniotomy, deroofing of the cyst and insertion of Ommaya catheter. The clinicopathological aspects of the cyst are discussed.